Improving Science Learning Outcomes through the TPACK Approach in Class V Students of SDN 1 Besani - Yeni Pratiwi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study in particular was to improve science learning outcomes for fifth grade students of Elementary School 1 Besani, Leksono District, Wonosobo Regency in the first semester of the 2020/2021 school year, through the application of the TPACK approach. "This research was carried out for 3 cycles. By looking at the pre-cycle data, the data from the results of the first, second and third cycle assessments, there was an increase in learning outcomes and completeness in each cycle. The percentage of completeness of students which was only 43% in the initial conditions, increased to 71.4% in cycle I, 85,7% in cycle II and 92,8% in cycle III. From the increase in the value of these students it can be said that the learning outcomes of students have increased. So the authors can draw the conclusion that through the application of the TPACK approach can improve science learning outcomes Animal Classification Material by Type of Food in class V Elementary School 1 Besani, Leksono District, Wonosobo Regency in the first semester of the 2020/2021 school year.